2024
DOI: 10.5802/crmeca.138
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of Koopman operator methods for system identification and predictions

Abstract: We give convergence and cost estimates for a data-driven system identification method: given an unknown dynamical system, the aim is to recover its vector field and its flow from trajectory data. It is based on the so-called Koopman operator, which uses the well-known link between differential equations and linear transport equations. Data-driven methods recover specific finite-dimensional approximations of the Koopman operator, which can be understood as a transport operator. We focus on such approximations g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…In case of an ODE, the set X is often assumed to be compact and forward-invariant and the probability measure is the standard Lebesgue measure, cf. Zhang and Zuazua (2021).…”
Section: Finite-data Bounds On the Approximation Error: Nonlinear Sdesmentioning
confidence: 99%
See 4 more Smart Citations
“…In case of an ODE, the set X is often assumed to be compact and forward-invariant and the probability measure is the standard Lebesgue measure, cf. Zhang and Zuazua (2021).…”
Section: Finite-data Bounds On the Approximation Error: Nonlinear Sdesmentioning
confidence: 99%
“…We briefly comment on this assumption and first note that forward invariance of X can be weakened, if one is only interested in estimates for states contained in X, see also Zhang and Zuazua (2021, Section 3.2). Moreover, if the dynamics obey an ODE, it was shown that the Koopman operator can indeed be extended to a strongly continuous semigroup on L 2 μ (X), see also Zhang and Zuazua (2021). Second, the assumption of invariance of the underlying probability measure is satisfied for a broad class of SDEs, see, e.g., Risken (1996).…”
Section: Finite-data Bounds On the Approximation Error: Nonlinear Sdesmentioning
confidence: 99%
See 3 more Smart Citations